Measurement of rapid landscape fragmentation in Iskandar Malaysia - Barau, Aliyu Salisu (2015)
Scientific projections have revealed that rapid and capital driven low-density urbanisation grossly undermines local and global environmental sustainability, with these effects set to become even more devastating in the near future. Landscape’s socio-ecological functions and services are bound to be affected by this form of rapid urban-industrial growth. The national planning instruments of countries such as Malaysia do not envisage some of the effects of this form of urbanisation on the landscapes. This study examines the problem of rapid fragmentation of landscape in Iskandar Malaysia as a special economic zone. The study adapted multiple data collection methods and various data analyses. The methods include field-based observations, public perceptions, and expert surveys, while land use and land cover data as well as capital-influx data were also analysed. This process helped the study to effectively measure the multiple dimensions of the study problem. The land use datasets for 2006 and 2010 were analysed using 11 landscape metrics to compute changes in landscape structure characteristics – area, shape, edge, diversity, connectivity, and contiguity. The study findings suggested that between 2006 and 2010, Iskandar Malaysia witnessed rapid changes in its landscape composition and configuration. The sharp increase in built-up areas from 13.5% in 2006 to 26.3% in 2010 has affected social and ecological processes in a number of ways. This capital driven rapid urbanisation has affected agricultural landscapes, mangroves and unprotected forests. Field observations revealed that landscape fragmentation has negatively affected upland ecosystems, landscape aesthetics, public safety, and landscape experiences. Public perceptions on effects of the fragmentation varied with people’s area of residence, age, and gender. The study also engages with broader sustainability discourse by establishing links between fragmentation of landscapes and urban morphology change, increasing carbon emissions, and humanwildlife conflict. Others include road users’ safety, land tenure, gentrification of ecological resources, public health, and environmental human rights issues. Thus, landscape fragmentation analysis is crucial to unravelling the complexities of urbanisation, globalisation, human-land interactions, and science and policy in the new urban age. Finally, the study underscores the need to entrench urban planning practices that reflect on and respect local environmental, cultural and social values of landscapes in order to achieve transformation to sustainable urbanisation in the emerging economies.